IABSE Task Group 3.1 Benchmark Results. Part 2: Numerical Analysis of a Three-Degree-of-Freedom Bridge Deck Section Based on Experimental Aerodynamics. Issue 3 (2nd July 2020) - Diana, Giorgio; Stoyanoff, Stoyan; Aas-Jakobsen, Ketil; Allsop, Andrew; Andersen, Michael; Argentini, Tommaso; Cid Montoya, Miguel; Hernández, Santiago; Jurado, José Ángel; Katsuchi, Hiroshi; Kavrakov, Igor; Kim, Ho-Kyung; et al.
Abstract: IABSE Task Group 3.1 has the mandate to define reference results for the validation of methodologies and programs used to study both stability and buffeting responses of long-span bridges. To this end, the working group set up a benchmark procedure consisting of several steps with increasing complexity to define reference results useful for this validation. The simplest step (1.1a) was presented in Part 1. In this paper (Part 2), the contributions and reference results of the second sub-step (1.1c) are discussed. It consists of the simulation of the aeroelastic response of a three-degree-of-freedom bridge deck section forced by turbulent wind, using experimental aerodynamic coefficients measured in a wind tunnel. The increase in complexity, compared to the previous step, involves the experimental definition of unsteady force coefficients that are defined in a limited range of reduced velocities, and inclusion of the lateral motion and horizontal turbulent wind velocity components. Comparison of the different outputs, obtained by Task Group 3.1 participants with the same input data, is presented, revealing differences that are not always negligible. Moreover, the increase in complexity of the test case results in larger spreads of the results compared to the fully analytical case, analysed in Part 1.